1996
DOI: 10.1093/infdis/174.1.105
|View full text |Cite
|
Sign up to set email alerts
|

Comparable Growth of Virulent and Avirulent Mycobacterium tuberculosis in Human Macrophages In Vitro

Abstract: The relative virulence and avirulence of Mycobacterium tuberculosis strains H37Rv and H37Ra were previously defined using animal infection models. To investigate host species' specificity of mycobacterial virulence, growth of the 2 M. tuberculosis strains in human monocyte-derived macrophages in vitro was studied. Mycobacterial growth was evaluated by acid-fast staining, electron microscopy, and colony-forming units (cfu) assay. As expected, the 2 strains demonstrated significantly different growth rates in mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 17 publications
5
46
1
Order By: Relevance
“…Even though H37Ra and H37Rv differ in trafficking within macrophages, and the number of H37Ra bacilli colocalized with lysosomes was significantly more than that of H37Rv bacilli, the overall pattern of colocalization of these two strains in different knockdown cell lines remained the same. Further, H37Ra and H37Rv has similar growth rates in human monocyte-derived macrophages (56). Moreover, the relative mRNA expression pattern of responding LSNRs in PBMCs from diseased and close contacts relative to healthy individuals compliments experimental findings (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Even though H37Ra and H37Rv differ in trafficking within macrophages, and the number of H37Ra bacilli colocalized with lysosomes was significantly more than that of H37Rv bacilli, the overall pattern of colocalization of these two strains in different knockdown cell lines remained the same. Further, H37Ra and H37Rv has similar growth rates in human monocyte-derived macrophages (56). Moreover, the relative mRNA expression pattern of responding LSNRs in PBMCs from diseased and close contacts relative to healthy individuals compliments experimental findings (Fig.…”
Section: Discussionsupporting
confidence: 76%
“…Microscopic examination revealed that each phagocyte contained between two and four acid-fast bacteria. This level of infection is similar to that observed by others working with avirulent strains of M. tuberculosis [19,22,39]. The number of passages did not signi¢cantly a¡ect the percentage of phagocytic macrophages, nor the number of acid-fast bacteria within infected cells.…”
Section: Recovery Of Viable Cells From Macrophagessupporting
confidence: 89%
“…These results also call for the integration of theoretical and experimental approaches to understand the temporal and spatial roles of signaling and macrophage migration in Mtb granuloma formation. (Graham & Clark-Curtiss, 1999;Manca et al, 1999;Silver et al, 1998;Zhang et al, 1998) (Paul et al, 1996;Zhang et al, 1998) Simulated experimental scenarios for macrophage activation that depend on the timing of IFN-γ and TNF signaling relative to infection. "Infection Outcome" refers to the success or failure of macrophage responses, measured by the number of intracellular bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter g bLIP scales the effect of the iron pool (in the subsaturation range) on the rate of bacterial growth. The logistic term ensures that the population does not exceed a plausible MOI, above a maximal population we set at 50 bacteria per cell (Paul et al, 1996;Zhang et al, 1998).…”
Section: Simulated M Tuberculosis Infectionmentioning
confidence: 99%